The Donor or the Recipient? Profiles of Students according to Their Perception of the Essence of University Social Responsibility - A Pilot Study Report - Hanna MACKIEWICZ; Edyta SPODARCZYK; Katarzyna I. SZELĄGOWSKA-RUDZKA (Communications of International Proceedings, 2021)
The main aim of the article is to present the opinion of a purposefully selected group of students from one of Polish universities on their understanding of the essence and characteristics of university social responsibility (USR). As part of detailed objectives, five profiles of students were defined (practical egoists, undecided egocentrics, we are connected by science, for and even against, striving for awareness), and probable relations between the university and its students in the process of implementing the concept of USR were indicated. It was found that the dominant group of respondents (practical egoists) are mainly interested in education and the opportunities of individual development (requiring them to be little involved); they present the attitude of ‘Recipients’. The smallest group (striving for awareness) are students also focused on education, but at the same time ready to engage in strictly social aspects. These students create the ‘Donors’ profile. A university that wants to actually implement the ideas of USR should intensify its activities for the development of the attitude of ‘Donors’ through education in the field of USR and through a good example of its own socially responsible practices addressed to internal and external stakeholders. The research is of a pilot nature, and the conclusions only concern the studied community.
Keywords: Corporate social responsibility; university social responsibility; higher education institutions; students’ profile.